Edukasi Pijat Bayi sebagai Antisipasi Awal Penanganan ISPA di Desa Majungan - Nofiya Nofiya; Yulia Paramita Rusady (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
This study aims to determine the effect of educational activities on the management of ARI through infant massage practices on increasing maternal knowledge and reducing complaints of coughs and colds in infants in Majungan Village. The research method used was descriptive with a mixed methods approach (quantitative and qualitative). The study subjects consisted of 25 mothers with infants aged 0–12 months. Data were collected through observation, interviews, and pre-test and post-test questionnaires. The results showed that the level of maternal knowledge increased from 28% to 88% after being provided with education and demonstrations of infant massage. In addition, 76% of mothers reported a decrease in complaints of coughs and colds in infants after routine infant massage for one week. Qualitative results indicate that this activity is not only physically beneficial, but also increases the role of mothers in the management of mild ARI and awareness of the importance of cleanliness and environmental health. Thus, education on the management of ARI through infant massage practices can be one of the supporting efforts in maintaining infant health, especially in areas with limited access to health services.